EFFECT OF TRACE ELEMENT COMPOSITION ON SOLUTION MINERALIZATION OF ELECTROCHEMICALLY ACTIVATED WATER IN ACIDIC MEDIUM - Zokirov K.R.; Abdullaev M.T.; Javokhir Y.I. (Western European Studies, 2024)
The article presents the results of research on the electrochemical activation of natural canal and tap water with low mineral content and the influence of the composition of microelements on the mineralization of the obtained solution
Keywords: canal water; tap water; electrochemically activated water; electrolyzer